Directed Sequencing of Plant Specific DNA Identifies the Dietary History of Four Species of Auchenorrhyncha (Hemiptera). (31st December 2021) - Cooper, W Rodney; Marshall, Adrian T; Foutz, Jillian; Wildung, Mark R; Northfield, Tobin D; Crowder, David W; Leach, Heather; Leskey, Tracy C; Halbert, Susan E; Snyder, James B
Abstract: Auchenorrhyncha (Hemiptera) includes several families of sap-feeding insects that tend to feed on a wide-range of host plants. Some species within Auchenorrhyncha are major agricultural pests that transmit plant pathogens or cause direct feeding damage. Nearly all pest Auchenorrhyncha are highly polyphagous, have mobile nymphs, and colonize crops from noncrop habitats. We examined whether methods for gut content analysis developed for more specialized Hemiptera identify dietary history of polyphagous Auchenorrhyncha. We used high-throughput sequencing of the plant genes trnF and ITS to examine the dietary history of Circulifer tenellus (Baker) (Cicadellidae), Colladonus geminatus (Van Duzee) (Cicadellidae), Colladonus montanus reductus (Van Duzee) (Cicadellidae), and Lycorma delicatula (White) (Fulgoridae). C. tenellus is a vector of the vegetable pathogens Candidatus Phytoplasma trifolii and beat curly top virus. Both Colladonus species are vectors of Ca. Phytoplasma pruni, the pathogen associated with X-disease of stone fruits. Lycorma delicatula is an invasive pest of grape and ornamentals in the eastern United States. Results showed spring hosts for C. tenellus included Brassicaceae, especially Sisymbrium sp. (tumble mustard), and spring hosts for both Colladonus species included Taraxacum sp. (dandelion). Gut content analysis also detected a decrease in host-breadth by L. delicatula from early to late instars. Results demonstrate that directed sequencing of plant DNA identified the dietary history of leafhopper and planthopper pests. Expanded use of gut content analysis will help identify the noncrop sources of phytoplasma-infected C. tenellus and Colladonus, and to examine seasonal changes in host shifts by L. delicatula.